Мусульманська культура кримських татар кінця XIX – початку XX ст.: рецепція Михайла Коцюбинського - Філянін, Є. (Чорноморська минувшина, 2023)
У статті розглянуто рецепцію Михайла Коцюбинського кримськотатарської культури. У 1890-х – початку 1900-х рр. письменник здійснив ряд подорожей до Криму, де він провів загалом два роки свого життя. Проаналізовано твори, що були написанні під враженнями від цих подорожей: «В путах шайтана»,«На камені» та «Під мінаретами». Вони відобразили особливості авторського сприйняття політичного, соціального та релігійного життя кримських татар та ісламу. The article examines Mykhailo Kotsiubynskyi’s reception of Crimean Tatar culture. In the 1890s and early 1900s, the author made several trips to Crimea, where he spent two years. The works that were written under the impression of these trips ("In the Shaytan's Chains", "On the Stone" and "Under the Minarets") are analyzed. They reflect the peculiarities of the author's perception of the political, social, and religious life of the Crimean Tatars and Islam. Attention is drawn to Mykhailo Kotsyubynsky's sufficiently good awareness of Tatar culture, especially for a person not native to Crimea. The narrative reflected on the pages of these short stories was present in the field of view of the Ukrainian audience during the Ukrainian-centric period, which in Ukrainian historiography is called "Ukrainian national revival". Back then information about the Muslim culture in the Ukrainian public discourse was represented in a limited way. Emphasis is placed on the presence of Ismail Gasprinsky`s Jadidism ideas in the Crimean society of the period. The importance of Mykhailo Kotsiubynskyi`s reception of the Muslim culture for the intellectual history and understanding of the perception of Islam by Ukrainians in the late 19th and early 20th centuries is explained.